Integration of knowledge sharing and training transfer to enhance sales promotion girls’ performance for Islamic products: A qualitative study‎ - Marjani, Marjani; Hapsari, Indri; Bugis, Hairudin; Asmaela , Asmaela; Elvira , Elvira; Sharman, Sharman; Manan, Dahran (Journal of Islamic Economics Lariba, 2025)
IntroductionIn today's competitive marketing environment, knowledge sharing and effective training transfer have become essential strategies for enhancing employee performance. This study investigates how these two mechanisms influence the performance of Sales Promotion Girls (SPGs) for Unilever’s Islamic product lines in Kendari City, Indonesia. ObjectivesThe research aims to examine the roles of knowledge collecting and knowledge donating, as well as the transfer of training outcomes, in strengthening SPG communication and sales skills.MethodUsing a qualitative-descriptive approach, data were collected through 25 in-depth structured interviews, participant observations, and document reviews involving selected SPG participants and supervisors. Thematic analysis was conducted manually using the interactive model, encompassing data reduction, data display, and conclusion drawing.ResultsThe findings reveal that formal knowledge collecting—mainly through structured training sessions—improves understanding of personal selling concepts and Unilever’s Islamic products. Informal knowledge sharing, including peer discussions, enhances practical skills but still faces challenges in conceptual depth. The study also finds that knowledge donating, although beneficial, is hindered by time constraints, uneven knowledge levels, and limited organizational recognition. Additionally, the transfer of training—delivered by Unilever’s internal supervisors and brand-specific trainers—is significantly influenced by hands-on field practice, collaborative coworker support, and motivational incentives, especially recognition from management for successfully applying training content.ImplicationsThese findings highlight the importance of integrating formal and informal knowledge-sharing mechanisms with practical training transfer strategies. The study implies that companies should provide applied learning opportunities and structured appreciation programs to foster a more collaborative and adaptive work environment that supports SPG performance.Originality/NoveltyThis research offers novel insights into how knowledge dynamics and training transfer operate within the marketing of Islamic (halal-certified) products in an emerging economy. Specifically, it contributes to the limited literature on frontline personnel development—such as Sales Promotion Girls (SPGs)—by highlighting how value-driven knowledge sharing and Sharia-aligned training practices enhance communication and sales effectiveness. This contextualized contribution bridges gaps in Islamic marketing literature, where most studies focus on consumer behavior or branding, rather than internal HRD mechanisms supporting faith-based marketing implementation.